Endoscopic removal of the Bravo pH capsule because of severe odynophagia - Azar, Riad (2003)
Purpose: Bravo pH monitoring is an innovative wireless system that allows ambulatory assessment of esophageal acid exposure using a radiotelemetery capsule. The device is attached to the distal esophagus by deployment of a locking pin through esophageal mucosa that has been pulled by suction into a small cup in the side of the capsule. Typically patients have minimal discomfort while the device is attached, and it eventually sloughs from the mucosa spontaneously. We reviewed clinical features and outcomes of patients who required endoscopic dislodgement of the device to determine predisposing characteristics and optimal methods for removal. Methods: Our institutional database was queried to identify patients who required endoscopic removal of the Bravo capsule. Clinical characteristics, management methods, and outcomes were extracted from endoscopy reports, clinical data forms, and pH study results. Results: A total of 118 patients underwent pH monitoring with the Bravo system over a 21 month period. 4 (3.4 %) required upper endoscopy for removal of the capsule because of severe symptoms within 2–8 days of attachment. Conclusions: In a small minority of patients, severe odynophagia necessitates endoscopic dislodgement of the Bravo capsule. All patients in this series had refractory or atypical symptoms, often pain, that had minimal assocation with reflux events on the pH study. Dislodgement of the device with a snare (without electrocautery) is advisable if initial attempts at gentle pressure with the endoscope are unsuccessful, as endoscopic pressure alone may result in stripping of the esophageal mucosa and bleeding